2009
DOI: 10.1089/end.2008.0531
|View full text |Cite
|
Sign up to set email alerts
|

Task Deconstruction Facilitates Acquisition of Transurethral Resection of Prostate Skills on a Virtual Reality Trainer

Abstract: For the acquisition of transurethral resection skills, task deconstruction is superior to full-task training alone, in training novices on the virtual reality TURP trainer. Such a study provides more validity evidence to the unique value of simulation in the urology minimally invasive curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Multiple studies have been conducted throughout the development of the University of Washington VR TURP simulator (Medical Education Technologies Inc, Sarasota, FL. 6,[9][10][11][12][13] These studies demonstrated a strong construct and discriminate validity, realistic blood loss simulation, and improved outcomes with task deconstructions versus full task-training. A similar approach was taken in the development of the resident exposure to transurethral surgical options for BPH GreenLight VR simulator.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted throughout the development of the University of Washington VR TURP simulator (Medical Education Technologies Inc, Sarasota, FL. 6,[9][10][11][12][13] These studies demonstrated a strong construct and discriminate validity, realistic blood loss simulation, and improved outcomes with task deconstructions versus full task-training. A similar approach was taken in the development of the resident exposure to transurethral surgical options for BPH GreenLight VR simulator.…”
Section: Discussionmentioning
confidence: 99%
“…In an era when many educators feel that deconstruction of a task is important for its teaching [2][3][4], this type of assessment may allow another avenue to improve the performance of a specific task or skill. Furthermore, the intra-corporeal suturing task (often learned in a box trainer) is an essential skill in MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Current laparoscopic box trainers use time and precision as standard metrics for assessment of performance [1]. In contrast, analysis of motion in the performance of deconstructed segments [2][3][4] of a defined surgical task may allow for real-time assessment of surgical skills and enhance formative assessment and education. While previous publications have described analysis of the motion in the overall completion of a task [5], to our knowledge, none have addressed such analysis for deconstructed segments of a task in laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 However, a certain level of basic knowledge is required for each procedure, and thus, modules to train part tasks that require a high level of automaticity are preferable. 30,34 The TURPsim provides whole procedure with different levels of difficulty and part-task practices, such as bleeding control and resection of the medial lobe.…”
Section: Discussionmentioning
confidence: 99%